2005
DOI: 10.1128/iai.73.11.7442-7449.2005
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Complement Activation and Leukocyte Adherence asNippostrongylus brasiliensisDevelops within the Murine Host

Abstract: Complement activation and C3 deposition on the surface of parasitic helminths may be important for recruitment of leukocytes and for damage to the target organism via cell-mediated mechanisms. Inhibition of complement activation would therefore be advantageous to parasites, minimizing damage and enhancing migration through tissues. The aim of this study was to determine ex vivo if complement activation by, and leukocyte adherence to, the nematode Nippostrongylus brasiliensis change as the parasite matures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…In addition, tumor-specific Abs may earmark tumor cells for killing by eosinophils via mechanisms similar to those demonstrated in studies of immunity to helminthic parasites (29). Our recent studies have demonstrated that migration of parasitic helminths in vivo can be impeded by eosinophils, and eosinophil attachment to larvae occurs rapidly and early in primary infections via complement C3 (30,31). However, at least in the Nippostrongylus brasiliensis parasitic model, Ab is not the main mechanism of recognition and attachment of eosinophils to helminth larvae (L. A. Dent, unpublished data).…”
Section: Discussionmentioning
confidence: 67%
“…In addition, tumor-specific Abs may earmark tumor cells for killing by eosinophils via mechanisms similar to those demonstrated in studies of immunity to helminthic parasites (29). Our recent studies have demonstrated that migration of parasitic helminths in vivo can be impeded by eosinophils, and eosinophil attachment to larvae occurs rapidly and early in primary infections via complement C3 (30,31). However, at least in the Nippostrongylus brasiliensis parasitic model, Ab is not the main mechanism of recognition and attachment of eosinophils to helminth larvae (L. A. Dent, unpublished data).…”
Section: Discussionmentioning
confidence: 67%
“…IgE is denatured by heat and excluded from precipitates prepared by salt precipitation at 35% saturation. Complement has been shown to be important for immunity to parasitic infections (54-56), and T. spiralis NBL are potent activators of complement (57). Furthermore, mouse eosinophils express functional complement receptors (58).…”
Section: Discussionmentioning
confidence: 99%
“…The genotypes of these mice were initially confirmed by M. Botto, who developed the Cfh Ϫ/Ϫ strain, and then reconfirmed by M. E. Woodman following completion of these studies. Both the Cfh Ϫ/Ϫ and Bf Ϫ/Ϫ strains have been used extensively by others for a variety of infection and other studies (2,23,32,56,63,66,67,82,90,91). The Botto laboratory provided these mouse strains to the Stevenson and Wooten laboratories, where the experiments described herein were performed.…”
Section: Methodsmentioning
confidence: 99%